ISLAMIST MOVEMENTS IN MOROCCO AND THEIR TYPOLOGY - Bouyahya, Driss (European Scientific Journal, ESJ, 2015)
The Islamist movements are far from homogenous. Pluralistic by nature, Moroccan Islamism can be divided into two groups: The Party of Justice and Development (Hizbo al- adala wa- Tanmia, PJD) under the direction of Abdelilah Benkiran, and Justice and Charity (al- adl wal- Ihsan, JC) led by Mohamed Abbadi. All groups and organizations that constituted Islamist movements have different and diverse objectives. While the nonpolitical groups have no concrete political objectives, they have a number of goals closely linked to the religious and moralistic dimension of Islam. On the other hand, the Islamist political movements, which are the subject of this study, target the restructuring of state- society relations in the image of Islam’s early golden years; others raised issues of equity and justice in open public discourse. The study traces back the birth and the growth of Islamist movements, mainly apolitical Salafists and militants, whereas the Islamist political movements that grow from a group to a party have evolved drastically and differently.